Evolution law of pore characteristics in microwave-assisted acidification induced fracturing shale based on low field nuclear magnetic resonance technology - He LI; Jiaxiang LIU; Baiquan LIN; Shiliang SHI; Wei YANG; Yi LU; Jiexin LU; Meng LIU (Meitan xuebao)
Low porosity and permeability of shale reservoir is the main factor restricting the efficient extraction of shale gas, nowadays, intensive fracturing and permeability enhancement technology is mostly used to modify the pore structure of shale reservoir, aiming to improve the permeability of shale body. Microwave heating has the ability of fracturing shale and gas desorption, but there are defects such as low penetration depth, local overheating, and fracture closure; acidizing has the advantages of efficiently unblocking shale pore space and greatly increasing permeability, but it is difficult for acid to enter microfissures, and it is too dependent on the initial degree of shale pore space development. Microwave-enhanced acid etching can effectively combine the advantages of the two, through the coupling effect of thermal stress, dissolution fracturing synergistically fractured shale body, to achieve better penetration effect. The shale was treated by three methods: microwave, acidification and microwave-enhanced acid etching, and the changes in pore structure between different intensities of the same method and different methods were compared using 1H-NMR detection. The results showed that the corresponding T2 spectral area of micropores and small pores (adsorption pores) of shale under the three treatments increased or decreased differently, decreased under acidification, increased under microwave and microwave-enhanced acid etching, and the increase of microwave was higher than that of microwave-enhanced acid etching; The corresponding T2 spectral area of the medium and large pores (seepage pores) increased continuously, and the increase in magnitude was as follows in descending order: acidification, microwave-enhanced acid etching, and microwave. Comprehensive observation of the changes in the T1-T2 spectra led to the conclusion that the process of penetration enhancement is the process of “pore opening” and “pore expansion”. The main role of microwave “open hole”, the main role of acidification “pore expansion”, microwave enhanced acid etching so that “open hole”, “pore expansion” The synergistic effect of microwave-enhanced acid etching is significant and shows better effect of increasing permeability. The change trend of porosity and pore throat and permeability under different treatments is consistent, and the overall trend shows an increasing trend, which proves that the three treatments are effective in increasing the permeability of shale, and the size of permeability is strongly correlated with the development of porosity and pore throat. The reduction of fractal dimension of microwave-enhanced acid-etched shale is the largest (4.203%), which is twice as much as that of acidizing treatment and 10 times as much as that of microwave treatment. The reduction of fractal dimension indicates a smoother pore interior, which reduces the possibility of methane adsorption and provides better conditions for shale gas recovery.